2014
DOI: 10.1105/tpc.114.129502
|View full text |Cite
|
Sign up to set email alerts
|

Nod Factor Receptors Form Heteromeric Complexes and Are Essential for Intracellular Infection inMedicagoNodules

Abstract: Rhizobial Nod factors are the key signaling molecules in the legume-rhizobium nodule symbiosis. In this study, the role of the Nod factor receptors NOD FACTOR PERCEPTION (NFP) and LYSIN MOTIF RECEPTOR-LIKE KINASE3 (LYK3) in establishing the symbiotic interface in root nodules was investigated. It was found that inside Medicago truncatula nodules, NFP and LYK3 localize at the cell periphery in a narrow zone of about two cell layers at the nodule apex. This restricted accumulation is narrower than the region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
72
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…The potential for MtNFP and MtLYK3 to provoke defense responses has been suggested as a reason why the accumulation and interaction of these two proteins are highly restricted in nodules [27]. The authors have suggested that the localization of MtNFP and MtLYK3 to just two cell layers is achieved through transcriptional control combined with high protein turnover [27]. In our N. benthamiana experiments, the attenuation of the MtNFPMtLYK3-induced cell death response, by co-expressing MtLYR3 (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The potential for MtNFP and MtLYK3 to provoke defense responses has been suggested as a reason why the accumulation and interaction of these two proteins are highly restricted in nodules [27]. The authors have suggested that the localization of MtNFP and MtLYK3 to just two cell layers is achieved through transcriptional control combined with high protein turnover [27]. In our N. benthamiana experiments, the attenuation of the MtNFPMtLYK3-induced cell death response, by co-expressing MtLYR3 (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…This response depends on the presence of the intracellular domains of both proteins, and the kinase activity of MtLYK3/LjNFR1, but is independent of Nod factor [25,26]. The potential for MtNFP and MtLYK3 to provoke defense responses has been suggested as a reason why the accumulation and interaction of these two proteins are highly restricted in nodules [27]. The authors have suggested that the localization of MtNFP and MtLYK3 to just two cell layers is achieved through transcriptional control combined with high protein turnover [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the interaction of two NF receptors, NFP and LYK3, has been reported. One study indicates that the interaction of NFP and LYK3 was detected in the heterologous N. benthamiana system and that their coexpression causes cell death (PietraszewskaBogiel et al, 2013), and another study reveals that NFP and LYK3 form heteromeric complexes at the cell periphery in nodules (Moling et al, 2014). Therefore, it is probable that the GTP-bound ROP10 forms a protein complex with NFP and LYK3.…”
Section: Discussionmentioning
confidence: 99%
“…Nod factor receptors, which include Lysine motif domain-containing receptorlike kinase3 (LYK3) and Nodulation factor perception (NFP) in Medicago truncatula and Nodulation factor receptor1 (NFR1) and NFR5 in Lotus japonicus, are plasma membrane-localized receptor-like kinase and kinase-like (RLK) proteins (Amor et al, 2003;Smit et al, 2007;Haney et al, 2011;Moling et al, 2014) consisting of an intracellular kinase domain and an extracellular region with two or three chitin-binding Lys motifs (LysM). LysM domains bind Nod factors through their chitin backbone (Petutschnig et al, 2010;Broghammer et al, 2012) and are implicated in Nod factor recognition specificity .…”
mentioning
confidence: 99%